Penerapan Slow Deep Breathing Untuk Menurunkan Keletihan pada Pasien Chronic Kidney Disease: Studi Kasus - Mufaj, Elda Nurfadila; Siti Ulfah Rifa'atul Fitri; Sandra Pebrianti (Jurnal Medika Nusantara, 2024)
Fatigue is the most common physical symptom felt by chronic kidney failure patients. Manifestations of fatigue are the body's inability to carry out routine activities, lethargy, and feeling tired all the time. Non-pharmacological therapy that can reduce fatigue is slow deep breathing relaxation therapy. To determine the intervention for providing slow deep breathing relaxation therapy in chronic kidney failure patients with fatigue. This research design is a case study using nursing care. Mr. I is 64 years old suffering from chronic kidney failure stage v who experiences problems with nursing fatigue. The intervention provided is by providing pharmacological and non-pharmacological therapy, slow deep breathing relaxation therapy. This study used the Functional Assessment of Chronic Illness Therapy-Fatigue Scale instrument. Fatigue complaints decreased with an increase in fatigue score. Before being given therapy, the slow deep breathing reaction was at a score of 22.6 became 40.33 after being given therapy for 3 days. Slow deep breathing can be given as an alternative non-pharmacological therapy which has the effect of reducing fatigue. It is hoped that nursing students or nurses in inpatient rooms can provide this therapy as a non-pharmacological intervention for chronic kidney failure patients with fatigue.